Arthroscopic Suture Fixation With Autograft Augmentation Reconstruction for Delayed Tibial Avulsion Fractures of the Posterior Cruciate Ligament. Issue 8 (25th August 2020) - Bi, Mingguang; Zhao, Chen; Chen, Jihang; Hong, Zheping; Wang, Zhen; Gan, Kaifeng; Tong, Yu; Bi, Qing
Background: The optimal surgical treatment of delayed avulsion fractures of the posterior cruciate ligament (PCL) is still controversial. Purpose: To evaluate the clinical results of arthroscopic suture fixation of tibial avulsion fractures of the PCL with autograft augmentation reconstruction. Study Design: Case series; Level of evidence, 4. Methods: From January 2013 to February 2017, we treated 15 patients with delayed tibial avulsion fractures of the PCL arthroscopically through posteromedial and posterolateral portals. The PCL and avulsion bone fragment were fixed with No. 2 nonabsorbable FiberWire sutures that were pulled out through a single tibial bone tunnel and fixed on a small Endobutton. Concomitantly, anatomic PCL augmentation reconstruction was performed, and the graft was pulled out through the same tunnel and fixed with an interference screw. Knee stability was assessed using the posterior drawer test, and the side-to-side difference was determined using a KT-1000 arthrometer with 134 N of posterior force at 30° of knee flexion. The International Knee Documentation Committee (IKDC) 2000 subjective form and Lysholm scale were used to evaluate clinical outcomes at follow-up. Overall, 12 patients were enrolled for analysis. The mean follow-up period was 34.4 months (range, 26-49 months). Results: At the final follow-up, 2 patients encountered 10° terminal flexion limitations. All patients had negative posterior drawer test results. The KT-1000 arthrometer side-to-side difference was significantly decreased from 8.25 ± 1.96 mm preoperatively to 1.08 ± 0.86 mm at the last follow-up ( P < .001). The mean IKDC and Lysholm scores, respectively, increased from 54.67 ± 7.13 and 53.50 ± 7.90 preoperatively to 91.13 ± 3.78 and 94.25 ± 3.32 at the final follow-up ( P < .001 for both). Conclusion: Arthroscopic suture fixation with autograft augmentation reconstruction for delayed tibial avulsion fractures of the PCL showed good clinical stability and function in this study.